Crosstalk between osteoblasts and endothelial cells co-cultured on a polycaprolactone-starch scaffold and the in vitro development of vascularization - Santos, Marina I. (2009)
The reconstruction of bone defects based on cell-seeded constructs requires a functional microvasculature that meets the metabolic demands of the engineered tissue. Therefore, strategies that augment neovascularization need to be identified. We propose an in vitro strategy consisting of the simultaneous culture of osteoblasts and endothelial cells on a starch-based scaffold for the formation of pre-vascular structures, with the final aim of accelerating the establishment of a vascular bed in the implanted construct. Human dermal microvascular endothelial cells (HDMECs) were co-cultured with human osteoblasts (hOBs) on a 3D starch-based scaffold and after 21 days of culture HDMEC aligned and organized into microcapillary-like structures. These vascular-like structures evolved from a cord-like configuration to a more complex branched morphology, had a lumen and stained in the perivascular region for type IV collagen. Genetic profiling of 84 osteogenesis-related genes was performed on coculture vs. monoculture. Osteoblasts in co-culture showed a significant up-regulation of type I collagen and immunohistochemistry revealed that the scaffold was filled with a dense matrix stained for type I collagen. In direct contact with HDMEC hOBs secreted higher amounts of VEGF in relation to monoculture and the highest peak in the release profile correlated with the formation of microcapillary-like structures. The heterotypic communication between the two cell types was also assured by direct cell– cell contact as shown by the expression of the gap junction connexin 43. In summary, by making use of heterotypic cellular crosstalk this co-culture system is a strategy to form vascular-like structures in vitro on a 3D scaffold.